Novel fully human high-affinity anti-TREM2 antibody shows efficacy in clinically relevant Alzheimer´s mouse model - Markus Kraller; Julia Faßbender; Ammar Jabali; Joseph Kroeger; Barbara Fink; Bastian Popper; Martin Ungerer; Miriam A. Christlmeier (Alzheimer’s Research & Therapy)
Abstract Background New drugs to treat Alzheimer´s disease (AD) are urgently needed. Human triggering receptor expressed on myeloid cells 2 (hTREM2) is a validated drug target which is genetically associated with AD. Existing anti-hTREM2 antibodies were raised in animal immune systems, and subsequently humanized, which may incur immunological complications upon repeated preventive or therapeutic applications in vivo in AD patients. In addition, anti-hTREM2 antibodies should be optimized for both, efficacy and safety. Methods A novel fully human monoclonal brain-targeting anti-hTREM2 antibody M07-TFN was created. Binding affinities, cell viabilities, and agonist potencies were investigated on rhTREM2 and in human microglia. Transcytosis assays modeled blood–brain barrier translocation (BBB). Behavior tests were carried out in 5 × familiar AD (5xFAD) mice of both genders, to test for brain function and cognition as well as hippocampus-dependent spatial memory using the Barnes maze. In addition, amyloid plaque formation was determined on brain sections at the end of the study. Results M07-TFN showed higher binding affinities and stronger activation of hTREM2 signaling than all previously described anti-hTREM2 antibodies. p-Syk activation was increased 30-fold in hTREM2-overexpressing HEK293 cells and fourfold in human microglia cells compared to baseline. Human microglia viability significantly improved after stress testing. M07-TFN showed strong BBB translocation in a human BBB model, and exerted cross-reactivity to the mouse TREM2 stalk region, which allowed us to investigate M07-TFN directly in an AD mouse model. In 5xFAD mice, M07-TFN resulted in improved novel object location and better spatial orientation and memory, and significantly reduced plaque load. Additional safety investigations in mice showed no negative effects on blood cells or major organs. Conclusion Compared to existing humanized anti-hTREM2 antibodies that have been investigated in clinical trials, M07-TFN showed best-in-class affinities and agonist potencies. Being a fully human anti-hTREM2 antibody, M07-TFN holds the promise of reduced immunogenicity for use in human patients.